Investigating the ultrastrctural and viscoelastic properties of whole blood, with specific focus on erythrocytes , in poorly controlled type 2 diabetes - Bester, Janette (University of Pretoria, 2025)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2018.